Simulation research on the bottom crash test of the battery pack base on an vehicle - DAI Jiangliang; MENG Xiangyu; CHEN Qi (Jixie qiangdu, 2025)
ObjectiveTo achieve the goal of accurately and effectively assessing the structural strength and the safety and health status of battery cells during bottom crash tests of battery packs.MethodsA numerical test model was established by using Abaqus software based on explicit dynamics theory and the finite element method, this model was used to calculate the displacement, equivalent plastic strain, and energy distribution of the structure.ResultsThe test results showed that the deformation shape, intrusion amount, and strength status of the crashed components were highly consistent with the simulation results, it indicates that the simulation model could accurately simulate and represent the dynamic response characteristics and damage mechanisms of the battery pack structure. Additionally, the mechanical response characteristics and energy distribution of the system and components during the test were studied through simulations. It was demonstrated that the system adhered to the principle of energy conservation. The simulation results indicated that 80.96% of the total energy was converted into strain energy in the crashed components, and the energy absorption ratio of the crashed components was directly proportional to the intrusion depth, it reveals the improvement direction for the underbody protection design, which is to reduce the intrusion of battery cells by designing an underbody protection solution with a high proportion of energy absorption. Furthermore, the maximum impact force 27 299 N of the ball head on the bottom of the battery pack was obtained, providing a theoretical reference for the mechanical performance design of bottom protection schemes for battery packs.